Student engagement with school: Critical conceptual and methodological issues of the construct - Appleton, James J.; Christenson, Sandra L.; Furlong, Michael J. (Psychology in the schools, 2008)
Research supports the connection between engagement, achievement, and school behavior across levels of economic and social advantage and disadvantage. Despite increasing interest and scientific findings, a number of interrelated conceptual and methodological issues must be addressed to advance this construct, particularly for designing data‐supported interventions that promote school completion and enhanced educational outcomes for all students. Of particular concern is the need to (a) develop consensus on the name of the construct, (b) identify reliable measures of the dimensions of the construct, and (c) complete the construct validation studies needed to move research and intervention forward. © 2008 Wiley Periodicals, Inc.